Beyond good intentions: lessons on equipment donation from an African hospital - Stephen RC Howie; Sarah E Hill; David Peel; Momodou Sanneh; Malick Njie; Philip C Hill; Kim Mulholland; Richard A Adegbola
OBJECTIVE: In 2000, a referral hospital in the Gambia accepted a donation of oxygen concentrators to help maintain oxygen supplies. The concentrators broke down and were put into storage. A case study was done to find the reasons for the problem and to draw lessons to help improve both oxygen supplies and the success of future equipment donations. METHODS: A technical assessment of the concentrators was carried out by a biomedical engineer with relevant expertise. Semi-structured interviews were undertaken with key informants, and content analysis and inductive approaches were applied to construct the history of the episode and the reasons for the failure. FINDINGS: Interviews confirmed the importance of technical problems with the equipment. They also revealed that the donation process was flawed, and that the hospital did not have the expertise to assess or maintain the equipment. Technical assessment showed that all units had the wrong voltage and frequency, leading to overheating and breakdown. Subsequently a hospital donations committee was established to oversee the donations process. On-site biomedical engineering expertise was arranged with a nongovernmental organization (NGO) partner. CONCLUSION: Appropriate donations of medical equipment, including oxygen concentrators, can be of benefit to hospitals in resource-poor settings, but recipients and donors need to actively manage donations to ensure that the donations are beneficial. Success requires planning, technical expertise and local participation. Partners with relevant skills and resources may also be needed. In 2002, WHO produced guidelines for medical equipment donations, which address problems that might be encountered. These guidelines should be publicized and used.